MANAJEMEN PENDIDIKAN PAUD AL- FATH SABANG - Bustami .; Murniati .; Cut Zahri Harun (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Early childhood education today has become the need of society. Although early childhood education, including education level of recognition, but education has contributed a lot to the development of children's education. This study aims to determine the implementation of the management of early childhood education made Al-Fath Sabang. This research uses descriptive method with a qualitative approach to data collection tool while using interviews, observation and documentation study questionnaire. As for the subjects in this study is the element that includes the school principal and teachers in early childhood Sabang Al-Fath, elements of the parents. The results showed that: (1) Planning early childhood education programs in school of Al-Fath, was generally well conceived, it has the look of the planningprogram of educational activities in accordance with the provisions of a plan of activities. (2) Organization of Al-Fath in early childhood, was publicly reflects the relevance of the ability and skills to the needs of education personnel. (3) The implementation of early childhood education in Al-Fath directed in the learning process goes well, effective and fun. (4) Supervision conducted by the two surveillance systems, namely: the direct supervision andcontrol of functional superiors. Supervisor oversight conducted by the Principal, while the functional supervision conducted by the School Trustees.Keywords : Management Education and early childhood